The Complete Mitochondrial DNA Sequence of Scenedesmus obliquus Reflects an Intermediate Stage in the Evolution of the Green Algal Mitochondrial Genome - Nedelcu, Aurora M.; Lee, Robert W.; Lemieux, Claude; Gray, Michael W.; Burger, Gertraud (Genome Research, 2000)
Two distinct mitochondrial genome types have been described among the green algal lineages investigated to date: a reduced–derived,Chlamydomonas-like type and an ancestral,Prototheca-like type. To determine if this unexpected dichotomy is real or is due to insufficient or biased sampling and to define trends in the evolution of the green algal mitochondrial genome, we sequenced and analyzed the mitochondrial DNA (mtDNA) ofScenedesmus obliquus. This genome is 42,919 bp in size and encodes 42 conserved genes (i.e., large and small subunit rRNA genes, 27 tRNA and 13 respiratory protein-coding genes), four additional free-standing open reading frames with no known homologs, and an intronic reading frame with endonuclease/maturase similarity. No 5S rRNA or ribosomal protein-coding genes have been identified inScenedesmus mtDNA. The standard protein-coding genes feature a deviant genetic code characterized by the use of UAG (normally a stop codon) to specify leucine, and the unprecedented use of UCA (normally a serine codon) as a signal for termination of translation. The mitochondrial genome of Scenedesmus combines features of both green algal mitochondrial genome types: the presence of a more complex set of protein-coding and tRNA genes is shared with the ancestral type, whereas the lack of 5S rRNA and ribosomal protein-coding genes as well as the presence of fragmented and scrambled rRNA genes are shared with the reduced–derived type of mitochondrial genome organization. Furthermore, the gene content and the fragmentation pattern of the rRNA genes suggest that this genome represents an intermediate stage in the evolutionary process of mitochondrial genome streamlining in green algae.[The sequence data described in this paper have been submitted to the GenBank data library under accession no. AF204057.]